The influence of profitability and growth on dividend policy with firm size as a control variable in the oil and gas subsector listed on the Indonesian Stock Exchange for the 2020-2024 period - Riyandi Riyandi; Hari Sulistiyo; Irvan Yoga Pardistya (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to analyze the effect of profitability and company growth on dividend policy, with firm size as a control variable, in oil and gas subsector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The study employs a quantitative research approach using secondary data obtained from annual reports and applies logistic regression analysis. The findings indicate that profitability and company growth simultaneously affect dividend policy. Partially, profitability has a significant effect on dividend policy, whereas company growth does not have a significant effect. Furthermore, the results show that the independent variables explain 40.4% of the variation in dividend policy. These findings suggest that companies with higher profitability are more likely to distribute dividends, while company growth is not a primary consideration in determining dividend policy. Keywords: Profitability; Growth; Firm Size; Dividend Policy